Periwayatan Hadis : Teknik, Bentuk, Syarat dan Metode yang Digunakan - Jusmiati; Idrus, Sulkifli (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
Hadith is the second source of Islamic teachings after the al-Qur'an, which is used as a guide and controller in the lives of Muslims. In the branch of science called Ulumul Hadith, there is a way to narrate a hadith properly and correctly to avoid mistakes in narrating the hadith. Hadith narration technique is a method or method used by someone in the activity of receiving and conveying hadith, as well as relying on the hadith to a series of transmitters using certain terms or symbols. There are two forms of narrating hadith, namely, narration with lafadz and narration with meaning. Muhadditsin has studied the conditions that must be fulfilled by a narrator in receiving and conveying hadith. Then, in carrying out hadith narration, the majority of scholars divide them into eight methods of narration, namely, as-sima' min lafdzhi as-syaikh (hearing from the teacher's words), al-qiraatu 'ala as-shaykh (reading to the sheikh), ijazah, munawalah (submission ), al-kitabah (notes), al-I'lam (announcement), testament, and al-wijadah (acquisition).